Identification and characterization of a novel chromosome-encoded aminoglycoside O-nucleotidyltransferase gene, ant(9)-Id, in Providencia sp. TYF-12 isolated from the marine fish intestine - Yu, Yan; Zhang, Runzhi; Pan, Wei; Sheng, Xinyi; Chen, Susu; Wang, Junjun; Lu, Junwan; Bao, Qiyu; Hu, Yunliang; Jiang, Pengfei; Huang, Dawei (Frontiers in Microbiology, 2024)
BackgroundThe mechanisms underlying the resistance of the genus Providencia to aminoglycosides are complex, which poses a challenge for the efficient treatment of infectious diseases caused by these pathogens. To help clinicians treat infections more effectively, a more comprehensive understanding of antibiotic resistance mechanisms is urgently needed.MethodsPlates were streaked to isolate bacteria from the intestinal contents of fish. The standard agar dilution method was used to determine the minimum inhibitory concentrations (MICs) of the antimicrobial agents. Molecular cloning was carried out to study the function of the novel antibiotic inactivation gene ant(9)-Id. The kinetic parameters of ANT(9)-Id were measured by a SpectraMax multifunctional microplate reader. Whole-genome sequencing and bioinformatic analysis were conducted to elucidate the sequence structure and evolutionary relationships of similar genes.ResultsThe novel aminoglycoside O-nucleotidyltransferase gene ant(9)-Id was encoded on the chromosome of a species-unclassified isolate designated Providencia sp. TYF-12, which was isolated from the intestine of a marine fish. Among the 11 aminoglycosides tested, ant(9)-Id was resistant to only spectinomycin. The MIC of spectinomycin for the recombinant strain carrying ant(9)-Id (pUCP20-ant(9)-Id/DH5α) increased 64-fold compared with that of the control strain (pUCP20/DH5ɑ). ANT(9)-Id shares the highest amino acid (aa) identity of 46.70% with the known drug resistance enzyme ANT(9)-Ic. Consistent with the MIC results, ANT(9)-Id showed high affinity and catalytic efficiency for spectinomycin, with a Km of 8.94 ± 2.50 μM and a kcat/Km of 26.15 μM−1·s−1. This novel resistance gene and its close homologs are conserved in Providencia strains from various sources, including some of clinical significance. No mobile genetic elements (MGEs) surrounding the ant(9)-Id(−like) genes were identified.ConclusionThis work revealed and characterized a novel spectinomycin resistance gene, ant(9)-Id, along with its biological features. Identifying novel resistance genes in pathogens can assist in rational medication use and the identification of additional antimicrobial resistance mechanisms in microbial populations.